Bacteriological analysis of water in municipal schools of Feira of Santana/BA (Research, Society and Development, 2021)
The research aimed to evaluate if the water in drinking fountains of municipal schools in three neighborhoods of Feira de Santana/BA followed the parameters for coliform absence. The samples were analyzed in duplicate contemplating 16 schools, where the water was collected directly in the troughs after asepsis with 70% alcohol in a glass jar with 10% sodium thiosulfate being evaluated in the period equal to 24 hours. The technique used for the identification of total coliforms and thermotolerant was that of Multiple Tubes, in which the samples that presented coliforms followed to perform the biochemical tests to identify the isolated species. Among the schools evaluated 37.5% detected total coliforms and 62.5% did not present this enteric agent. It is concluded that part of the schools participating in this survey do not follow the standards of water potability established by the Consolidation Ordinance n°of september 28, 2017.